The natural history of small-duct primary sclerosing cholangitis. - Björnsson, E; Olsson, R; Bergquist, A; Lindgren, S; Braden, B; Chapman, R; Boberg, K; Angulo, P (2008)
BACKGROUND and AIMS: The long-term prognosis of patients with small-duct primary sclerosing cholangitis (PSC) remains incompletely characterized. We aimed at determining the natural history and long-term outcomes of a large number of patients with small-duct PSC. METHODS: Data from 83 patients with well-characterized small-duct PSC from several medical institutions in Europe and the United States were combined. Each patient with small-duct PSC was randomly matched to 2 patients with large-duct PSC by age, gender, calendar year of diagnosis, and institution. RESULTS: The median age at diagnosis in both groups was 38 years (61% males). Nineteen (22.9%) of the 83 patients with small-duct PSC progressed to large-duct PSC in a median of 7.4 (interquartile range [IQR], 5.1-14) years. One patient with small-duct PSC who progressed to large-duct PSC was diagnosed with cholangiocarcinoma but after progression to large-duct PSC; 20 patients with large-duct PSC developed cholangiocarcinoma. Patients with small-duct PSC had a significantly longer transplantation-free survival compared with large-duct PSC patients (13 years [IQR, 10-17] vs 10 years [IQR, 6-14], respectively; hazard ratio, 3.04; 95% confidence interval: 1.82-5.06; P < .0001). Two patients with small-duct PSC who underwent liver transplantation had recurrence of small-duct PSC in the graft 9 and 13 years, respectively, after transplantation. CONCLUSIONS: Small-duct PSC is a disease of progressive potential but associated with a better long-term prognosis as compared with large-duct PSC. Small-duct PSC may recur after liver transplantation. Cholangiocarcinoma does not seem to occur in patients with small-duct PSC, unless the disease has progressed to large-duct PSC.